860. A Proposed Standard for Hospital Bioaerosol Monitoring in Avoiding Nosocomial Mould Infections. (31st December 2020) - Seiler, Garret T; Ostrosky-Zeichner, Luis; Ferguson, Lance; Boston, Kelly; Grant, Mike; Koehn, Jan
Abstract: Background: Recent nosocomial outbreaks of mould infections have been linked to bioaerosols. Active and passive environmental sampling is a primary method of quantifying airborne contamination in the hospital, but currently there are no standardized Occupational Exposure Limits (OELs) for the avoidance of nosocomial infections. Methods: Between March 2016 and December 2019, 186 post-construction/post-cleaning air samples were collected to measure particle counts based on defined size criteria Lighthouse handheld Particle Counter) and viable air fungal cultures (Anderson single stage N6 Viable Particulate Sampler) across wards of a 1, 082 bed hospital in Houston, Texas, and compared with outdoor controls. Areas were cleared for occupancy if the ≤ 0.3micron particle counts were reduced by the expected efficacy of the HVAC unit and if indoor fungi airborne concentrations in CFU/m³ were also reduced or did not exceed the outdoor ambient reference levels for each separate day of site assessment. Results: The mean counts of particles ≤ 0.3microns were as follows: floors 37, 427.50 (-32% reduction), operating rooms 8, 163.88 (95% reduction), OR sterile core 15, 001.31 (89% reduction), ICU 7, 640.15 (93% reduction), radiology suites 1, 046.25 (97% reduction), and outpatient areas 17, 891.58 (82% reduction). The table indicates the reported mean density (CFU/m³) data and species of fungi isolated in viable bioaerosol samples, 13 of which matched outdoor reference isolates. The mean density of outdoor cultures was 292.37 compared to all indoor units 24.53 (91.61% reduction), floors 25.44 (91.3% reduction), ICUs 28.19 (90.4% reduction), radiology suites 22.5 (92.3% reduction), and ORs 12.79 (95.6% reduction). During this time, no nosocomial fungal infections or outbreaks were documented for the institution. Table 1: Mean Density (cfu/mm3) of Fungal Species per Location Conclusion: An indoor air quality standard comprised of particle count data reduced by the expected efficacy of the operating HVAC unit and also existing indoor viable fungi in units of CFU/m³ that did not exceed the outdoor reference could potentially be correlated with avoidance of nosocomial mould infections. Disclosures: Luis Ostrosky-Zeichner, MD, Amplyx (Scientific Research Study Investigator)Astellas (Consultant, Scientific Research Study Investigator, Other Financial or Material Support, Non-branded educational speaking)Biotoscana (Consultant, Other Financial or Material Support, Non-branded educational speaking)Cidara (Consultant, Scientific Research Study Investigator)F2G (Consultant)Gilead (Consultant)Mayne (Consultant)Octapharma (Consultant)Pfizer (Other Financial or Material Support, Non-branded educational speaking)Scynexis (Consultant, Grant/Research Support, Scientific Research Study Investigator)Stendhal (Consultant)Viracor (Consultant)